Influence of social support and self-efficacy on training transfer in 5-star hotels: An exploratory qualitative study - Basnet, Dinesh; Dumaru, Krisha (Academia Journal of Research and Innovation, 2026)
In the hospitality industry, particularly at five-star hotels, the quality of service is a key determinant of customer satisfaction, making it crucial to have effective training programs. This study seeks to examine the role of different social support, organizational, peer, and supervisor support, and self-efficacy in training transfer in the five-star hotel industry in Nepal. It is about the role of these within the workplace and how they relate to their application of knowledge and skills acquired in the training, and this will impact their overall job performance. This study was exploratory in nature and utilized a qualitative approach with semi-structured interviews with hotel employees, managers, and supervisors. These interviews provided detailed information regarding experiences with participants and the effect of a variety of supports and levels of self-efficacy on their ability to transfer new capabilities to their jobs. Thematic analysis was used to identify key themes and patterns, which led to a deeper understanding of factors that affect training transfer. Results of the study indicate that supervisor support is of critical importance to reinforce training practically. More frequent feedback and follow-up on the use of new abilities by the supervisor led to greater training transfer for employees. Peer support also emerged as an important element in fostering a non-threatening environment for teamwork and confidence among staff. Moreover, self-efficacy, or self-confidence to achieve success, has been shown to play a significant role in the transfer of training. Those with higher self-efficacy were more likely to use new skills in their work and were more likely to be proactive in their work. This study is original in terms of its selection of the hotel industry sector (five-star hotels) in Nepal, which has not been studied much recently in the field of training transfer. Using a qualitative approach, this research provides rich, contextualized insights into the unique cultural and organizational challenges faced in Nepal’s hospitality sector. It provides a detailed analysis of the effect of support systems and self-efficacy on the successful transfer of training in this context. The importance of creating a supportive working atmosphere and boosting employee self-efficacy to create good training outcomes is highlighted in this study. These findings can be applied in hotel management, which means the need for continuous supervision of the supervisor engagement, peer collaboration, and confidence-building tactics can greatly increase the return on investment in employee training programs.